The interaction of chlororganic pollutants with snow cover in Antarctica - V. I. Bogillo; M. S. Bazylevska (Ukrainian Antarctic Journal, 2008)
The snow cover in Antarctica is the global sink for high-toxik chlororganic pollutants (COP) from their anthropogenic sources in tropics and midlatitudes. The snow surface/air (KIA) and mineral surface/water (Km) partition coefficients, and related changes of the enthalpies in these processes have been calculated for COPs identified in air, seawater and snow cover of Antarctica. Influence of COPs nature on the snow–air scavenging ratio. It has been shown that ice/air interface introduces main contribution into decrease of total COPs fugacity in snow cover in Central Antarctica, whereas the contribution of the organic phase in the cover is more essential one in the coastal regions. The desorption kinetics for COPs from the snow cover in boundary air layer corresponds to the kinetics for diagenesis of the cover, it can be predicted on basis of independent measurements of the diagenesis’ kinetics at different temperatures, and lifetime for COPs fromthe cover increases with growth of log KIA value for the COPs. Maximal fluxes of DDTs and polychlorobiphenyls from air on the snow cover in Antarctica are close to the same fluxes in Arctic and to peak’ values for world production and usage of the COPs. The temporal decline for COPs level in the Antarctic snow cover reflects the global reduction of their production and usage in the Southern Hemisphere. Intensity of the fluxes for the COPs from air into the Antarctic snow cover is reduced during latest decades and the process is closed to the equilibrium now. Although the COPs amount deposited in Antarctic snow is low in comparison with their global emission, the glaciers and snow cover in coastal regions of the continent and the islands are to be essential local sources for the re-emission of COPs in coastal waters of ocean, lakes and in the boundary atmospheric layer.